A survey for potential biological control agents of Pereskia aculeata Miller (Cactaceae) in Brazil reveals two new species of Horismenus Walker (Hymenoptera: Eulophidae) - Pikart, Tiago G.; Costa, Valmir A.; Hansson, Christer; Cristo, Sandra C. De; Vitorino, Marcelo D. (Zootaxa, 2017)
This paper deals with the description of two new species of Horismenus Walker (Hymenoptera: Eulophidae) from Brazil, parasitoids of larvae of Adetus analis (Haldeman) (Coleoptera: Cerambycidae). Both species are similar to Horismenus steirastomae (Girault), a species that also parasitizes cerambycids. Adetus analis is a pest of Sechium edule (Jacq.) Swartz (Cucurbitaceae), a minor crop in Brazil, Argentina and U.S.A., but also feeds in stems of Pereskia aculeata Miller (Cactaceae), an ornamental plant that has become a problematic weed species in Africa, where it was introduced. The two new Horismenus species are described, diagnosed, and compared to H. steirastomae.